2001
DOI: 10.1038/sj.ijo.0801603
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-related breathing disorders, loud snoring and excessive daytime sleepiness in obese subjects

Abstract: OBJECTIVE:To investigate the prevalence of sleep breathing disorders, loud snoring and excessive daytime sleepiness in a group of obese subjects, and to identify the predictors of obstructive sleep apnea (OSA) severity in these patients. SUBJECTS: A total of 161 consecutive obese patients (body mass index (BMI) ! 30.0 kgam 2 ), ranging between 30.0 and 67.3, represented by 57 men and 104 women, aged 16 ± 75 y. Forty (15 men and 25 women) age-matched (20 ± 70 y) nonobese (BMI`27 kgam 2 ) volunteers were also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
162
3
14

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(199 citation statements)
references
References 30 publications
15
162
3
14
Order By: Relevance
“…We would like to suggest that the discrepancy between men and women (confirmed by our unpublished data) may be due to differences in fat distribution (mainly subcutaneous in women and visceral in men) and hormonal milieu, and to a higher prevalence and severity of sleep-respiratory disturbances in obese males. 8 Indeed, visceral fat, rather than overall adiposity, has been demonstrated to predispose to the development of sleep apnoea in obese individuals. 19 In particular, it has been shown that sleep apneics obese patients have significantly higher amount of visceral fat, compared to nonsleep apneics obese controls, even though there was no difference between the two groups in terms of Diurnal PaCO 2 tension in obese women O Resta et al BMI, as well as the amount of both total and subcutaneous body fat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We would like to suggest that the discrepancy between men and women (confirmed by our unpublished data) may be due to differences in fat distribution (mainly subcutaneous in women and visceral in men) and hormonal milieu, and to a higher prevalence and severity of sleep-respiratory disturbances in obese males. 8 Indeed, visceral fat, rather than overall adiposity, has been demonstrated to predispose to the development of sleep apnoea in obese individuals. 19 In particular, it has been shown that sleep apneics obese patients have significantly higher amount of visceral fat, compared to nonsleep apneics obese controls, even though there was no difference between the two groups in terms of Diurnal PaCO 2 tension in obese women O Resta et al BMI, as well as the amount of both total and subcutaneous body fat.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several studies on diurnal hypoventilation in patients affected by obesity hypoventilation syndrome (OHS) have been performed, [4][5][6] whereas few data exist on diurnal PaCO 2 tension in apparently healthy nonsmoking obese patients. 7 It is noteworthy that several studies demonstrated a wide array of respiratory disturbances during sleep (hypoventilation, obstructive apnoea-hypopnoea events, and 'flow limitation') in obese individuals, 8,9 but no information is available about the possible relationship between diurnal PaCO 2 tension and sleep-respiratory disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…Resta et al (16) investigated 161 obese subject and 40 age-matched control subjects. They found that neck circumference in men, and BMI in women were strongest predictors of sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
“…The second group (group two) of 16 patients was treated with CPAP for at least two years. The polysomnography was performed according to the protocol of our sleep laboratory [3]. The diagnosis of OSAS was made according to ASDA criteria [4].…”
Section: Patientsmentioning
confidence: 99%